PENGARUH METODE EXPERIENTIAL LEARNING DAN METODE EGP (EMOSIONAL, GERAK CEPAT, DAN PEREVISIAN) TERHADAP KETERAMPILAN MENULIS CERITA PENDEK SISWA KELAS VIII SMPN 16 KOTA TANGERANG SELATAN - Wulandari, Adelia; Ediwarman; Ilmi Solihat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Abstract: Many students still face difficulties in writing short stories, especially in terms of developing ideas, plot, language, and imagination. This emphasizes the importance of implementing learning methods that support the creative writing process. The purpose of this study was to determine the effect of the experiential learning method, the effect of the EGP method (Emotional, Fast Action, and Revision), and the differences in the effects of both on the short story writing skills of class VIII students of SMPN 16 South Tangerang City. This research with a quantitative approach uses an experimental method with a Quasi Experimental Nonequivalent Control Group Design. The research sample was conducted using the Purposive Sampling technique, namely class VIII C as the experimental class and VIII D as the control class. Data were obtained from the results of the pretest and posttest of short story writing skills and through statistical calculations with the help of SPSS version 25. The results of the t-test showed that the significance of the experiential learning method and the EGP method were both 0.000 <0.05 so that Ha was accepted and Ho was rejected. There was an increase in the average pretest and posttest results in the experiential learning method of 16.17 points while in the EGP method it was 10.63 points. This shows that the experiential learning method is superior to the EGP method (Emotional, Fast Action, and Revision) in improving the short story writing skills of class VIII students of SMPN 16 South Tangerang City. Keywords: Write Short Stories, Experiential Learning Method, EGP Method (Emotional, Fast Movement, and Revision)